A communication network routing problem: Modeling and optimization using non-cooperative game theory - Dubey, Sapana P.; Kedar, Ganesh D.; Ghate, Suresh H. (Zielona Góra: Uniwersytet Zielonogórski)
We consider a communication network routing problem wherein a number of users need to efficiently transmit their throughput demand in the form of data packets (incurring less cost and less delay) through one or more links. Using the game theoretic perspective, we propose a dynamic model which ensures unhindered transmission of data even in the case where the capacity of the link is exceeded.
Keywords: communication network; routing problem; game theory; focal points; Nash equilibrium; Pareto optimal solution